Hybrid bulk and planar heterojunctions with electroluminescent quantum dots CdZnSeS and poly(dioctylfluorene) - Matvienko, O.O.; Kryzhanovska, O.S.; Savin, Yu.N.; Vovk, O.M.; Pogorelova, N.V.; Vashchenko, V.V. (Functional Materials, 2012)
Hybrid organic-quantum dot light emitting devices (QD-OLED) with bulk and planar heterojunctions based on poly(dioctylfluorene) and electroluminescent quantum dots CdZnSeS (QD) were obtained. The influence of QD concentration and the QD film morphology on the device electroluminescence was investigated. For QD-OLED with QD emissive bilayer, the device electroluminescent efficiency was higher compared to bulk heterojunction.